2020
DOI: 10.3390/antibiotics9090614
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Genes in Porcine Pasteurella multocida Are Not Associated with Its Antimicrobial Susceptibility Pattern

Abstract: Forty-eight Pasteurella multocida isolates were recovered from porcine pneumonic lungs collected from farms in “Castilla y León” (north-western Spain) in 2017–2019. These isolates were characterized for their minimal inhibition concentrations to twelve antimicrobial agents and for the appearance of eight resistance genes: tetA, tetB, blaROB1, blaTEM, ermA, ermC, mphE and msrE. Relevant resistance percentages were shown against tetracyclines (52.1% for doxycycline, 68.7% for oxytetracycline), sulphamethoxazole/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Regarding the bacterial isolates, a total of 90 bacterial isolates were identified from those 67 analysed animals, and AMR genes were detected in 52 isolates. Thus, in line with other studies [28,29], we observed that some of the AMRB did not have any of the AMR genes. This could be explained by the possible existence of other mechanisms of resistance such as chromosomal mechanisms that were not included as a target of this study.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the bacterial isolates, a total of 90 bacterial isolates were identified from those 67 analysed animals, and AMR genes were detected in 52 isolates. Thus, in line with other studies [28,29], we observed that some of the AMRB did not have any of the AMR genes. This could be explained by the possible existence of other mechanisms of resistance such as chromosomal mechanisms that were not included as a target of this study.…”
Section: Discussionsupporting
confidence: 93%
“…In the case of APP and PM, 13 and 12 clusters have been defined, respectively, according to their antimicrobial susceptibility pattern using a hierarchical clustering analysis. This multivariate statistical tool allows defining groups with similar antimicrobial susceptibility patterns in a visual and comprehensive way as recently published for Pasteurella multocida in swine [16], Escherichia coli in humans and animals [17], and uropathogenic Escherichia coli in humans [18]. The number of clusters for both bacteria could look very high, taking into account that the antimicrobial susceptibility pattern is favorable for many antimicrobials, but combinations of two or three antimicrobials with low antimicrobial susceptibility generated the observed clusters as published for other microorganisms [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…This multivariate statistical tool allows defining groups with similar antimicrobial susceptibility patterns in a visual and comprehensive way as recently published for Pasteurella multocida in swine [16], Escherichia coli in humans and animals [17], and uropathogenic Escherichia coli in humans [18]. The number of clusters for both bacteria could look very high, taking into account that the antimicrobial susceptibility pattern is favorable for many antimicrobials, but combinations of two or three antimicrobials with low antimicrobial susceptibility generated the observed clusters as published for other microorganisms [16][17][18][19]. The distribution of antimicrobial susceptibility observed for these respiratory pathogens clearly shows that a proper diagnostics and sensitivity testing should be performed for each clinical case.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of infections in which ESBLs are produced usually have quite an unpredictable course. E. coli is an example of a multidrug-resistant and ESBL-producing bacterium that can be the source of extremely severe infections [ 72 , 73 , 74 ]. As has previously been stated, some strains of E. coli can also cause very serious medical conditions connected with urinary and gastrointestinal tract and central nervous system [ 75 ].…”
Section: Introductionmentioning
confidence: 99%